A Functional Polymorphism in Accessible Chromatin Region Confers Risk of Non-Small Cell Lung Cancer in Chinese Population - Long, Jieyi; Long, Tingting; Li, Ying; Yuan, Peihong; Liu, Ke; Li, Jiaoyuan; Cheng, Liming (Frontiers in Oncology, 2021)
Background: The disease-associated non-coding variants identified by genome-wide association studies (GWASs) were enriched in open chromatin regions (OCRs) and implicated in gene regulation. Genetic variants in OCRs thus may exert regulatory functions and contribute to non-small cell lung cancer (NSCLC) susceptibility. Objective: To fine map potential functional variants in GWAS loci which contribute to NSCLC predisposition using chromatin accessibility and histone modification data, and explore their functions by a population study and biochemical experimental analyses. Methods: We mapped the chromatin accessible regions of lung tissue using data of assay for transposase-accessible chromatin using sequencing (ATAC-seq) in The Cancer Genome Atlas (TCGA), and prioritize potential regulatory variants within lung cancer GWAS loci by aligning with histone signatures using data of chromatin immunoprecipitation assays followed by sequencing (ChIP-seq) in Encyclopedia of DNA Elements (ENCODE). A two-stage case-control study with 1830 cases and 2001 controls was conducted to explore the associations between candidate variants and NSCLC risk in Chinese population. Bioinformatic annotations and biochemical experiments were performed to further reveal the potential functions of significant variants. Results: Sixteen potential functional single-nucleotide polymorphisms (SNPs) were selected as candidates from bioinformatics analyses. Three variants out of the 16 candidate SNPs survived after genotyping in stage 1 case-control study, and only the results of SNP rs13064999 were successfully validated in the analyses of stage 2 case-control study. In combined analyses, rs13064999 was significantly associated with NSCLC risk (additive model, OR = 1.17, 95%CI: 1.07-1.29, P = 0.001). Functional annotations indicated its potential enhancer bioactivity and dual-luciferase reporter assays revealed a significant increase in luciferase activity for the reconstructed plasmid with rs13064999 A allele, when compared to the one with wild-type G allele (PA549 ＜0.001, PSK-MES-1 = 0.004). Further electrophoretic mobility shift assays (EMSA) and super-shift assays confirmed a stronger affinity of HP1γ for the binding motif containing SNP rs13064999 A allele. Conclusion: These findings suggested that the functional variant rs13064999, identified by the integration of ATAC-seq and ChIP-seq data, contributes to the susceptibility of NSCLC by affecting HP1γ binding, while the exact biological mechanism awaits further exploration.